Evaluasi Rasionalitas Insulin Pada Pasien Diabetes Mellitus Tipe 2 Rawat Jalan di RSUD Kota Madiun Periode 2022 - Fitria Wahyuning Wulan; Lelly Winduhani Astuti; Fentyana Dwi Rilawati; Akbar Firdaus Syam (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to defects in insulin secretion, insulin action or both. Diabetes mellitus (DM) is currently a global health threat. Various epidemiological studies have shown an increase in the incidence and prevalence of DM in the world. Based on data from the profile of the East Java Health Office in 2021, it is estimated that DM patients in Madiun City rank fourth in the East Java region. . Objective: This research was conducted to determine the evaluation of the rationality of insulin in type 2 DM patients in the Outpatient Hospital of Madiun City Hospital for the period 2022. Methods: This research method is in the form of an observational research, retrospective data collection in the form of medical records of history of type 2 diabetes mellitus patients at Outpatient Hospital at RSUD Madison City. The total population in this study in the period January - December 2022 was 165 patients. Results: From the 62 type 2 DM patients who were outpatients at Madiun City Regional Hospital, it was found that 14.52% using single insulin and 12.90% used Detemir insulin. The use of the insulin combination was 85.48% and the Detemir – Aspart insulin combination was 58.06%. Conclusion: Evaluation of the rationality of insulin use showed that the correct drug was 100% and the correct dose was 93,55%.